MANAJEMEN PROGRAM PERCEPATAN BELAJAR (Studi Kasus di SMA Negeri 1 Wates Kulon Progo ) (JURNAL ILMIAH TUT WURI HANDAYANI, 2013)
The research is intended to know the preparation of the implementation, the management of students, t teachers and staff, curriculum, facilities, fund, result, the problems and the solution and the evaluation of the Acceleration Learning Program in SMA Negeri 1 Wates, Kulon Progo. Naturalistic Qualitative Approach is carried out in the research. The technique of the data collection is carried out through physical and non- physical observation, free but controlled interview on the basis on the principles of comparability, reliability and documentation. The credible data is achieved through the extended study time, persistence and source and triangulation method. Data legality is achieved by the search and writing the research result which is already approved by the research resource. The technique of data analysis is used simultaneously, that is, collection, reduction, datapresentation and drawing conclusion. The research result shows that the preparation, the management of students, teachers and staff, curriculum, facilities, funding has already met the Implementation Principle. Some of the Students Management still does not meet the Implementation Guidelines, for example, there are some students joining the program with IQ under 125, whereas theaccepted students should have at least IQ score of 125. The learning result of the Accelerated Learning Program in SMA Negeri 1 Wates in terms of the students’ achievement is reported to the parents including semester test result, National Examination Score and the number of graduates accepted in university which are not lower than those of the regular students. The problem that occurs includes the learning process disturbance because of the decrease of the students’ motivation and the candidates quality which does not yet meet the criteria for the Accelerated Study Program. To solve the problem, the school implements various learning process, decreasing unessential learning material , refreshing program at the end of the first semester and improving the system of new students recruitment. The evaluation of the Accelerated Learning Program in SMA Negeri 1 Wates is that the program has been implemented in accordance with the implementation procedures.